Assessment of Risks and Strategies in Disaster Risk Management in Nepal (Patan Pragya, 2025)
This paper scrutinizes the status and impact of disaster risk management in Nepal. The country is prone to natural calamities due to complicated and fragile geographical locations and unanticipated climate change impacts. The geographical locations are highly remote and fragile often face biggest challenges to response and prepare for disasters. The article aims to assess risks and strategies formulated to reduce the disasters including floods, earthquakes, cold waves, fire, droughts, and landslides that are threatening to the human security and property protection. Nepal’s geographical location and fragile ecosystem, poor infrastructure, deforestation and unplanned urbanization have been explored as the causes of disasters and its impact. Consequently, almost every part of the country is prone disaster risks. In response to such random disasters, both government and non-government agencies and organizations have endeavored to strategically address both natural and human induced disasters. The study has been accomplished based on secondary data drawn from diverse sources. Meanwhile, the approach to analyze the variables that relate to risks and strategies has been qualitative. Since the research is based on secondary data, the analysis of the themes distinctly tends to respond to the query how Nepal has been responding to such disasters and what strategies have been formulated to address the problem.